The Assessment of Intravascular Volume with Inferior Vena Cava and Internal Jugular Vein Distensibility Indexes in Children Undergoing Urologic Surgery. (2nd November 2018) - Bilgili, Beliz; Haliloglu, Murat; Tugtepe, Halil; Umuroglu, Tumay
ABSTRACT: Purpose: The purpose of this work is to assess the predictive value, for fluid responsiveness (FR), of the inferior vena cava distensibility index (IVC-DI) and internal jugular vein distensibility index (IJV-DI) in pediatric surgical patients. Material and Methods: Prior to being placed under general anesthesia, 24 surgical patients were enrolled. Baseline parameters were recorded with the patient in the semirecumbent position (Stage 1). Next, the passive leg raising (PLR) maneuver was carried out and a second measurement was recorded (Stage 2). Patients with an increase in the cardiac index (CI) of >10%, induced by PLR, were considered to be responders (R), otherwise they were classified as nonresponders (NR). At both stages, CI and DI of the IVC and IJV were measured. Results: Responders had higher IVC-DI and IVJ-DI than NR in stage 1 (both p <.001). In stage 2, IVC-DI and IJV-DI were not different in R and NR groups ( p =.164, p =.201). Utilizing cut-off values of > 22.7% for IVC-DI and > 25% for IJV-DI, these parameters had positive correlation coefficients, both in R and NR of, respectively, 0.626 and 0.929. Conclusions: The IVC-DI predicts FR in anesthetized pediatric patients and correlates well with the IJV-DI; both may be used as prediction markers of FR in children.